Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

N-substitution of polybenzimidazoles: synthesis and evaluation of physical properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (European Polymer Journal, 2009)
Series of N-substituted polybenzimidazoles (PBI) were synthesized using selective alkyl groups with varying bulk and flexibility, viz., methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. PBl-I based on 3,3'-diaminobenzidine (DAB) and isophthalic acid and PBI-Bul based on DAB and 5-tert-butyl isophthalic acid were chosen for N-substitution. Structural characterizations of substituted polymers by FT-IR and (1)H NMR revealed elimination of hydrogen bonding. Evaluation of their physical properties revealed that N-substitution rendered better solvent solubility in common organic solvents, more open polymer matrix, but reduced thermal properties in comparison to their respective parent PBI. 4-tert-butylbenzyl, methylene trimethylsilane or n-butyl group substituted polymers were soluble even in chlorinated solvents (CHCl(3) and TCE). Substantial variations in gas permeability of inert gases, He and Ar and attractive P(He)/P(Ar) selectivity, especially after methyl group substitution depicted potential of these materials for gas separation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; hydrogen bonding; N-Substitution; Polybenzimidazole

Investigation of gas permeation properties of systematically modified polybenzimidazoles by N-substitution - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Gas permeation behavior of a series of thermally stable N-substituted polybenzimidazoles by systematically varying bulk and flexibility of the substituent was investigated. Two different PBIs having variation in their acid moiety, viz., PBI-I (based on isophthalic acid) and PBI-BuI (based on 5-tert-butyl isophthalic acid) were selected for N-substitution by alkyl groups possessing different bulk and flexibility. These substituent groups were methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. Pure gas sorption and permeability using H(2), N(2), O(2), CH(4) and CO(2) were investigated and correlated with physical properties of formed polymers. Estimation of dual-mode sorption parameters, coefficients of sorption, permeability and diffusion for different gases provided an insight towards effects of nature of a substituent group and parent PBI on governing gas sorption and permeation properties. By changing the substituent group, diffusivity coefficients was found to vary to a larger extent than the solubility coefficient. This significantly enhanced gas permeability for different gases by 1.2-129 times than that of parent PBIs. The permselectivity P(O2)/P(N2) was increased (up to 237%), while for other gas pairs, it was decreased to a different extent. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; N-Substitution; Polybenzimidazole; Sorption

New N-substituted ABPBI: synthesis and evaluation of gas permeation properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Aromatic poly(2,5-benzimidazole), ABPBI was post-modified for the first time to produce organosoluble N-substituted ABPBI. This modification was carried out by N-substitution of ABPBI with bulky alkyl groups, viz., 4-tert-butylbenzyl and methylene trimethylsilyl in an attempt to utilize high rigidity of ABPBI towards gas permeation. These substituted polymers exhibited solubility in common organic solvents, enhancing their processability than ABPBI, which is soluble only in acidic solvents. Considerable decrease in chain packing density led to increase in gas sorption as that of unsubstituted ABPBI. The permeability of pure gases of commercial significance (He, H(2), N(2), O(2), CH(4) and CO(2)) were high, coupled with attractive selectivities. In comparison to conventional PBI, methylene trimethylsilyl substituted ABPBI led to considerably high (33 folds) CO(2) permeability with almost similar selectivity (P(CO2)/P(N2) approximate to 33). Feasibility of these N-substituted ABPBIs to be converted in to required membrane form along with its considerably higher permeation properties depicted the potential of this polymer to be used as gas separation material. Gas diffusion coefficients were estimated from solubility and permeability coefficient. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior caused by the substitution. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 5-benzimidazole); Diffusion; Gas permeation; N-Substitution; Poly(2; Sorption

Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid

Film forming polymeric ionic liquids (PILs) based on polybenzimidazoles for CO2 separation - Kumbharkar, Santosh C.; Bhavsar, Rupesh S.; Kharul, Ulhas K. (RSC Advances, 2014)
PILs are emerging as promising materials for CO2 capture. Film formation, which is a requisite for membrane formation, is induced in a family of PILs by N-substituting a rigid thermo-mechanically stable polybenzimidazole, followed by metathesis. This provided two IL groups per repeat unit of the PIL and enhanced the CO2 separation characteristics.

Investigation of gas permeation properties of film forming polymeric ionic liquids (PILs) based on polybenzimidazoles - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2014)
Polymeric ionic liquids (PILs) are emerging as new generation membrane materials for CO2 separation. Gas permeation properties of a recently developed PIL family based on three structurally different polybenzimidazoles (PBIs) possessing excellent film forming characteristics are reported. Effects of cationic backbone and anions on gas permeation properties of PILs using pure gases (He, H-2, N-2, CH4, and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. In comparison to the parent PBIs, PILs exhibited generally higher CO2 permeability, without largely affecting CO2 based selectivity. Some of these PILs exhibiting high PCO2/PCH4, selectivity and P-H2/P-CO2, approaching similar to 1 indicated dominance of CO2 sorption over diffusion. The CO2 sorption specificity of these PILs was distinctly observed based on their improved S-CO2/S-N2, S-CO2/S-CH4 and S-CO2/S-H2 selectivity than their parent PBIs. A large variation in permeation properties of PILs based on a common polycation but different anions indicated that anions play a crucial role on governing gas permeation properties of these PILs. (C) 2014 Elsevier B.V. All rights reserved
Keywords: Gas permeation; Membranes for CO2 separation; Polybenzimidazole; Polymeric ionic liquid

Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.